Increasing Scope of Search Incidental to Arrest - H. Frank Way Jr. (Washington University Law Quarterly, 1959)
One of the major problems in the law of search and seizure today is the increasing scope of search incidental to arrest. This problem is intimately connected with the decline in the use of warrants by law enforcement officers. In part this decline can be attributed to the vast urbanization and industrialization which has occurred in the United States in the last seventy-five years. Searches and seizures by warrants are undoubtedly easier in a more rural society than is found in the United States today. In the rural atmosphere of the United States from the founding of our nation until the post-Civil War period the absence of rapid means of communication and transportation did not necessitate the speed of action which law enforcement officers believe is demanded in the urban community. The result of this demand for quick action has been a decline in the use of the warrant. The decline in the warrant has intensified the problem of determining by a post-mortem the reasonable limits of search and seizure. Without the prior statement of probable cause and the particular description of the places to be searched and the things to be seized, law enforcement officers must use their own judgment of what constitutes reasonable physical scope of the search and seizure. Allowing for a certain area of disagreement which would be present whether a warrant were used or not, law enforcement officers have demonstrated a tendency to push the limits of the physical scope of search and seizure to the utmost.
Keywords: Search and seizure